PENGARUH PEMBERIAN EKSTRAK ETANOL DAUN BAWANG DAYAK (Eleutherine Palmifolia L. Merr) TERHADAP KADAR GULA DARAH MENCIT PUTIH (Mus muscullus) YANG DIINDUKSI GLUKOSA - Eka Kumalasari; Syifa Maharani; Aditya Maulana Perdana Putra (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Diabetes Mellitus (DM) is a collection of metabolic symptoms that arise in a person caused by an increase in blood glucose due to damage to insulin secretion or resistance to insulin or both. Diabetes mellitus medication can be either parenteral or oral which can cause side effects in long-term use such as mild diarrhea, bloating, fatigue acidosis, even hypoglycemic renal impairment. To prevent it can use alternative medicine using Dayak onion (Eleutherine palmifolia (L) Merr.). One of the active substances contained in the Dayak onion is the flavonoids. Flavonoids have antidiabetic activity through their functions as antioxidants. The study aims to determine the activity of Dayak scallion Extract (Eleutherine palmifolia (L) Merr.) To decrease blood sugar levels (Mus muscullus), which is glucose-induced. The research was conducted with research draft pre and post test with control group design. The mice used amounted to 25 male white mice that were divided into 5 groups i.e. negative control (CMC Na 0.5%), control positive (Glibenklamid 3 mg/kgBB), Dayak onion-leaf ethanol extract at a dose of 50 mg/kgBB, 100 mg/kgBB and 200 mg/kgBB. Observations of the decrease in blood sugar levels of each test group were conducted on the same day, 30 minutes, 60 and 90 after hyperglycemia. Results showed that Dayak onion leaves ethanol extract had activity as a lowering of blood sugar levels in glucose-induced white mice